Persoalan Yuridis Undang-Undang Nomor 40 Tahun 1999 tentang Pers - Ahmad Irzal Fardiansyah (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Press is an institution that has a strong influence on the forming of public opinion and efficacy of spreading information. Therefore, it is really strategic if press is empowered to spread positive information for public. However, in many cases crime of press in the Act Number 40, 1999regarding Press is not imposed by the reason of lex specialist. This article is going to answer the juridical problem in enforcing law regarding press. It shows that the act has not fulfilled the criteria as the act with lex specialist as it has no qualification of a crime as KUHP states it as KUHP is the main rule of crime regulation. Thus, in terms of trial involving press, judges persist to impose KUHP is correct. it is recommended that the act of Press as lex specialist should be revised on the Act by fulfilling the requirements that are proper to KUHP as the main source of criminal law for other laws.  Juridical Matters on The Act Number 40, 1999 on Press